О влиянии перинатального инфицирования на кальций-фосфорный гомеостаз и структурное состояние костной ткани у беременных = About influence of the perinatal infection on calcium-phosphorus homeostasis and structural condition of bone tissue in pregnant women - Gulsym S. Manasova; Alexandr A. Zelinsky; Sergei V. Derishov; Natalia V. Kuzmina (Kazimierz Wielki University, 2016)
Manasova Gulsym, Zelinsky Alexandr, Derishov Sergei, Kuzmina Natalia. О влиянии перинатального инфицирования на кальций-фосфорный гомеостаз и структурное состояние костной ткани у беременных = About influence of the perinatal infection on calcium-phosphorus homeostasis and structural condition of  bone tissue in pregnant women. Journal of Education, Health and Sport. 2016;6(4):271-280. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50199 http://ojs.ukw.edu.pl/index.php/johs/article/view/3470   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016.   УДК 618.33-022.7-06: 616.71-008.92   О ВЛИЯНИИ ПЕРИНАТАЛЬНОГО ИНФИЦИРОВАНИЯ НА КАЛЬЦИЙ-ФОСФОРНЫЙ ГОМЕОСТАЗ И СТРУКТУРНОЕ СОСТОЯНИЕ КОСТНОЙ ТКАНИ У БЕРЕМЕННЫХ   1Г. С. Манасова, 2А. А. Зелинский, 2С. В. Деришов, 3Н. В. Кузьмина   1Городской департамент здравоохранения, Одесса 2Одесский национальный медицинский университет 3КУ «Родильный дом №5», г. Одесса   Реферат В статье представлены результаты исследования кальций-фосфорного гомеостаза у беременных с верифицированным перинатальным инфицированием (ВПИ) и остеопеническим синдромом. Материалы и методы. В динамике обследовано3 группы беременных: с ВПИ и клиническими и/или ультразвуковими проявленими инфекции (I-A - 192 пациентки), с ВПИ и без каких-либо проявлений инфекции (I-Б - 43); 128 здоровых женщин вошли в группу контроля (II). Содержание общего (Са) и ионизированного кальция (Са ++), фосфора в крови и экскреция Са с мочой определялись фотометрическим методом; состояние костной ткани - методом ультразвуковой денситометрии. Результаты исследования. Выявлено снижение концентрации общего и ионизированного кальция по мере увеличения срока беременности в основной ((1,89 ± 0,03) и (1,67 ± 0,05) ммоль/л) и контрольной ((2,41 ± 0,02) во 2-м, (2,16 ± 0,03)- в 3-ем триместрах (р < 0,001)) группах;  у здорових женщин уровень кальция оставался в пределах физиологической концентрации, тогд как при ВПИ снижение его коцентрации было значительным со второго триместра. Изменения МПКТ у 9,78% беременных с ВПИ соответствовали остеопорозу уже при первичном обследовании, а у 71,91% - остеопеническому синдрому (ОПС). В группе контроля ОПС был выявлен только у 23,43% пациенток. Выводы. Концентрация кальция в крови по мере увеличения срока гестации характеризуется снижением и у здоровых беременных и у беременных с ВПИ; при инфицировании его уровень достоверно ниже. Вероятно, повышение потребности организма беременной в кальции при инфицировании не компенсируется физиологическими механизмами адаптации, характерными для здоровых женщин. Снижение МПКТ при ВПИ характеризуется более выраженными и более быстрыми темпами изменений по сравнению с аналогичными показателями в группе у здоровых беременных. Перинатальное инфицирование является одним из факторов риска развития остеопороза у беременных. Ключевые слова: беременность, костная ткань, кальций-фосфорный гомеостаз, инфицирование.   About influence of the perinatal infection on calcium-phosphorus homeostasis and structural condition of  bone tissue in pregnant women   1Gulsym Manasova, 2Alexandr Zelinsky, 2Sergei Derishov, 3Natalia Kuzmina   1Health Department of the City Council Odessa 2Odessa National Medical University, the Medical Faculty 3Communal Health Protection Institution "Maternity Hospital  №5", Odessa, Ukraine   Аbstract The article presents the results of calcium-phosphorus homeostasis study in pregnant women with verified perinatal infection (VPI) and osteopenic syndrome. Materials and methods. 3 groups of pregnant women were examined in dynamics. There were 192 patients with VPI and clinical and/or ultrasound manifestations of infections (I-A), 43 patients had  VPI without manifestations of  infection (I-B); 128 healthy women constituted the control group (II). The content of general and ionized calcium, phosphorus in blood, and urinarium calcium excretion were defined by photometric method; bone tissue state was examined by ultrasound densitometry. Results. The reduction of total and ionized calcium concentration took place with increasing gestational age ((1,89 ± 0,03) and (1,67 ± 0,05) mmol / l) and control ((2,41 ± 0,02) in the 2nd, (2,16 ± 0,03) - in the 3rd trimester (p <0,001)) groups.  Calcium levels in healthy women remained within the physiological concentrations, whereas calcium decrease was significant already in the 2nd trimester at VPI. BMD conformed osteoporosis in 9,78% of the women under observation with the VPI already at the initial examination and osteopenic syndrome (OPS) was identified in 71,91% of women. In the control group OPS was diagnosed in only 23,43% of the patients. Conclusions. Blood calcium concentration is characterized by decrease and depends on  increasing gestational age in all groups; calcium level is significantly lower at infected patients. Evidently, elevation of VPI pregnant women calcium needs is not compensated by the mechanisms of physiological adaptation, as against healthy women. Reduced of bone mineral density at infected womwn is characterized by more pronounced and rapid changes in comparison with the same indexes in  the group of healthy pregnant women.